Ocular and subcutaneous dirofilariasis in a Sri Lankan infant: an environmental hazard caused by dogs and mosquitoes - Senanayake, Manouri P.; Infaq, M. L. M.; Adikaram, S. G. S.; Udagama, P. V. (Paediatrics and International Child Health, 2011)
An 11-month-old infant presented with a subcutaneous nodule in the right cheek which was found by ultrasonography to be a worm. Following treatment with di-ethylcarbamazine, a worm emerged from the left upper eyelid which was confirmed to be Dirofilaria repens. Dirofilariasis usually manifests as a single lesion and is rare in infants.
Keywords: Dirofilaria repens; Infant; Ocular dirofilariasis; Subcutaneous dirofilariasis; mosquito populations; Dog